Rwanda’s food systems transformation: A diagnostic of the public policy landscape shaping the transformation process - Dusingizimana, Petronille; Kazungu, Jules; Lalui, Armin; Milani, Peiman; Munanura, James; Nsabimana, Aimable; Sindi, Julius Kirimi; Spielman, David J.; Umugwaneza, Maryse (International Food Policy Research Institute, 2022)
This paper provides a diagnostic of Rwanda’s food systems and the policy landscape that shapes it. It aims to inform national and local conversations on Rwanda’s food systems transformation—an idea that has attracted considerable attention in national consultations conducted in the run-up to the United Nations Food Systems Summit in September 2021, at the summit itself, and in the post-summit actions that Rwanda is now pursuing. A food system comprises the full range of actors and activities originating from agriculture, livestock, forestry, or fisheries, as well as the broader economic, societal, and natural environments in which they operate. An inclusive and sustainable food systems transformation is a process of growth and development that is profitable for the full range of individual actors engaged in the system, beneficial for society including marginalized and vulnerable groups, and advantageous for the natural environment. Rwanda’s journey towards a food systems transformation is well captured in Vision 2050, the National Strategy for Transformation (NST 1), and strategic plans for sectors such as agriculture, health, nutrition, commerce, and the environment. Their priorities are echoed in ongoing programs and investments of the government, its development partners, the private sector, and civil society. Nonetheless, there are still challenges facing Rwanda’s efforts to sustain and accelerate progress along this journey. Efforts to overcome these challenges call for a deeper and more significant shift in thinking—informed by the food systems perspective—that is highlighted by stronger multi-sectoral approaches to problem-solving. Overall findings suggest an opportunity for a tangible shift in how public policy in Rwanda approaches its food systems and how the systems contribute to the broader national transformation process. This means addressing how balances are struck—and tradeoffs are managed—between and among agriculture, nutrition, health, and the environment in the face of a climate crisis. It also means giving greater attention to the demand-side drivers in Rwanda’s food system, recognizing that singularly focused supply-side strategies rarely succeed in isolation. Finally, it means deepening the integration of policies and policy actors in the design and implementation phases of interventions that shape the food system. We offer several recommendations to translate abstract ideas into a coherent and focused set of actions in the policy space. 1. Strengthen existing entities and mechanisms rather than create new ones. 2. Develop a national food systems transformation strategy that is integrative, multi-sectoral, and action-oriented. 3. Innovate on existing programs. 4. Allow for learning through both success and failure. 5. Invest in rigorous impact evaluation. These actions aim to strengthen the policy environment that enables a truly broad-based food systems transformation. This enabling environment is itself an outcome of broad-based national conversations, integration across sectors, domains, and levels; and the encouragement of policy and program innovation.